Tap, move, shake turning your game ideas into iPhone & iPad apps - Moore, Todd (O'Reilly Media, 2011)
Introduces Xcode and Objective-C by guiding reader through hands-on development of a real game. Includes implementing game logic, sophisticated graphics, game physics, sound, and computer AI.
Includes index. - Print version record
Keywords: iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; Video games -- Design; Video games -- Programming; Application software -- Development; Objective-C (Computer program language); iPhone (Téléphone intelligent); Programmation; iPad (Ordinateur); Programmation; Jeux vidéo; Conception; Jeux vidéo; Programmation; Logiciels d'application; Développement; Objective-C (Langage de programmation); COMPUTERS; Software Development & Engineering; General; COMPUTERS; Programming; Apple Programming; Application software; Development; Computer games; Design; Video games; Programming